Metodologia de simulação numérica do comportamento térmico em equipamentos eletroeletrônicos - Sousa, Reginaldo Ribeiro de [UNESP] (2015)
When electronic equipment and devices are developed, the knowledge of all the features of this project is essential. Some electronic circuits have components with high thermal power dissipation, which can cause problems to the product developed. The electronic components have a limit on the temperature, such property is called junction temperature. If the junction temperature is exceeded, the electronic components will display inappropriate behavior or even a complete stop their activities. Ideally, the electrical design and thermal design concurrently advance in the development of the equipment in order to obtain an optimum product. A efficient way to meet the thermal performance of electronic equipment is through computer simulations in Computational Fluid Dynamics (CFD) software. However make use of this tool can be difficult. The difficulty is creating the numerical model. For this procedure is necessary to know some variables that are unknown. The thermal power dissipation of electronic components, not resistors or capacitors, but integrated circuits that has in its interior a very complex structure containing thousands or millions of transistors is an example. The complex structures of the geometries to be modeled that are inside electronic components and PCBs are other examples. In this context, this thesis proposes a methodology based on numerical correlations and experimental tests in order to know the device's temperature range designed running in a desired situation. The methodology is based on a correlation between the simplified numerical model and experimental test. The thermal simulation methodology presented in this thesis brings contributions to the thermal management in the design of electronic equipment. The approach allows doing numerical simulations of equipment for a desired scene and the results assist in project analysis, particularly in reliability and lifetime of electronic ...